Curative Effect and Survival Assessment Comparing Gemcitabine and Cisplatin Versus Methotrexate, Vinblastine, Doxorubicin and Cisplatin as Neoadjuvant Therapy for Bladder Cancer: A Systematic Review and Meta-Analysis - Wu, Tiange; Wu, Yuqing; Chen, Shuqiu; Wu, Jianping; Zhu, Weidong; Liu, Hui; Chen, Ming; Xu, Bin (Frontiers in Oncology, 2021)
Background: Neoadjuvant chemotherapy has been accepted as an effective curative treatment for muscle-invasive bladder cancer patients and has resulted in better survival outcomes than radical cystectomy or a cisplatin-based regimen. In the present study, we aimed to compare the two most commonly used cisplatin-based neoadjuvant chemotherapies, gemcitabine plus cisplatin and methotrexate plus vinblastine plus doxorubicin plus cisplatin, by summarizing and analyzing clinical data and outcomes of published research. Methods: We searched for qualified studies that compared these two types of neoadjuvant chemotherapy, including 4 randomized controlled trials and 14 retrospective studies. Data and information on pathological responses and long-term survival studies were extracted and analyzed separately. Results: A total of 18 studies with 3116 patients were selected from 1188 studies, which contained data on pathological complete response, pathological partial response, and overall survival. In contrast to the results of previous studies, there was no significant difference in pathological complete response (odds ratio, 0.97; 95% confidence interval, 0.81-1.15), pathological partial response (odds ratio, 0.85; 95% confidence interval, 0.72-1.14), and overall survival (hazard ratio, 0.99; 95% confidence interval, 0.83-1.17) between GC and MVAC in this meta-analysis. Conclusion: No significant differences were observed between GC and MVAC in the muscle-invasive bladder cancer treatment due to the similar curative effect and parallel long survival outcomes due to the similar curative effect and parallel long survival outcomes. The priority selection of GC or MVAC in the clinic should be guided by further investigation, and the clinical standard strategy still counts on the results of more randomized controlled trials in the future.